PENGARUH REKRUTMEN, DAN KOMITMEN ORGANISASI TERHADAP KINERJA KEPALA SEKOLAH DASAR KABUPATEN MANOKWARI - MINCE PARA’PAK (Universitas Negeri Jakarta, 2015)
The aim of this research is to examine the effect of recruitment and organizational commitment on job performance.The research was conducted to all of headmaster at the city of Manokwari by using a survey method with path analysis applied in testing hypothesis. The number of 91 headmasters as sample was selected by using Slovin formula. The result of research indicates: (1) there is direct effect of recruitment on job performance, (2) there is direct effect of organizational commitment on job performance, (3) there is direct effect of on job performance.Based on those finding it could be concluded that any changing or variation wich occured to the job performance of headmasters atManokwari Regency had been effected by recruitment and organizational commitment.